Iron Overload Induces Oxidative Stress, Cell Cycle Arrest and Apoptosis in Chondrocytes - Karim, Asima; Bajbouj, Khuloud; Shafarin, Jasmin; Qaisar, Rizwan; Hall, Andrew C.; Hamad, Mawieh (Frontiers in Cell and Developmental Biology, 2022)
Abstract: Clinical and experimental evidence point to the presence of considerable links between arthropathy, osteoarthritis (OA) in particular, and iron overload possibly due to oxidative stress and tissue damage. However, the specific cellular targets of iron overload-related oxidative stress in OA remain ambiguous. We examined the effects of iron overload on chondrocyte health using the C-20/A4 chondrocyte cell line. Cells were treated with increasing concentrations of ferric ammonium citrate (FAC) to mimic iron overload in vitro. Treated cells were assessed for cell viability, cycling, apoptosis, collagen II synthesis, and oxidative stress along with cellular iron content and the expression of key iron regulatory genes. FAC treatment resulted in an increase in ferritin expression and a significant decrease in the expression of hepcidin, ferroportin, transferrin receptors 1 (TfR1) and TfR2. Increased labile iron content was also evident, especially in cells treated with high FAC at 24 h. High doses of FAC treatment also induced higher levels of reactive oxygen species, reduced collagen II production, disrupted cell cycle and higher cell death as compared with untreated controls. In conclusion, findings presented here demonstrate that iron overload disrupts cellular iron homeostasis, which compromises the functional integrity of chondrocytes and leads to oxidative stress and apoptosis.